Calibrating the tree of vipers under the fossilized birth-death model - Šmíd, Jiří; Tolley, Krystal A (Scientific reports, 2019)
Scaling evolutionary trees to time is essential for understanding the origins of clades. Recently developed methods allow including the entire fossil record known for the group of interest and eliminated the need for specifying prior distributions for node ages. Here we apply the fossilized birth-death (FBD) approach to reconstruct the diversification timeline of the viperines (subfamily Viperinae). Viperinae are an Old World snake subfamily comprising 102 species from 13 genera. The fossil record of vipers is fairly rich and well assignable to clades due to the unique vertebral and fang morphology. We use an unprecedented sampling of 83 modern species and 13 genetic markers in combination with 197 fossils representing 28 extinct taxa to reconstruct a time-calibrated phylogeny of the Viperinae. Our results suggest a late Eocene-early Oligocene origin with several diversification events following soon after the group's establishment. The age estimates inferred with the FBD model correspond to those from previous studies that were based on node dating but FBD provides notably narrower credible intervals around the node ages. Viperines comprise two African and an Eurasian clade, but the ancestral origin of the subfamily is ambiguous. The most parsimonious scenarios require two transoceanic dispersals over the Tethys Sea during the Oligocene.
Keywords: Genetic Markers; Computational Biology; genetické markery; fylogeneze; Animals; výpočetní biologie; Viperidae; Biological Evolution; Fossils; Models, Biological; Sequence Analysis, DNA; biologická evoluce; Phylogeny; zkameněliny; biologické modely; zvířata; sekvenční analýza DNA